Unique Rifa‘iyah Interpretations of the Pillars of Islam: Analyzing Their Social and Religious Implications in Indonesia - Safii, Safii; Nurul Ain, Aiyuhan; Gumiandari, Septi; Nafi'a, Ilman (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
The formulation of the Five Pillars of Islam, widely accepted by the majority of Muslims, is not upheld by the Rifa‘iyah sect, who claim that there is only one such pillar. This obvious divergence from the majority view is strongly opposed by the leading religious organizations and has soured the social interactions between Rifa‘iyah and non-Rifa‘iyah communities in Indonesia. This article aims to understand: (1) the nature of the controversy surrounding the single pillar of Islam in Rifa‘iyah belief; (2) the factors that provoke this controversy; (3) the social impact of this controversy on Indonesian society. This research employs a qualitative methodology, with primary data sourced from the writings of Kiai Ahmad Rifa‘i and interviews with several Rifa‘iyah clerics. Findings show the difference is nominal, with faith testimony as the core and others as complements. However, misinterpretations and prejudices have fueled hidden conflicts between Rifa‘iyah and non-Rifa‘iyah communities. This study highlights the value of intellectual diversity in Islamic scholarship and provides practical recommendations to reduce social tensions, including promoting interfaith dialogue, integrating diverse theological perspectives into education, and fostering collaborative community activities. It fosters a more tolerant understanding of Islam in Indonesia.